The Peculiar Longevity of Things Not So Bad - Gilbert, Daniel T.; Lieberman, Matthew D.; Morewedge, Carey K.; Wilson, Timothy D. (Psychological Science, 2004)
Intense hedonic states trigger psychological processes that are designed to attenuate them, and thus intense states may abate more quickly than mild states. Because people are unaware of these psychological processes, they may mistakenly expect intense states to last longer than mild ones. In Study 1, participants predicted that the more they initially disliked a transgressor, the longer their dislike would last. In Study 2, participants predicted that their dislike for a transgressor who hurt them a lot would last longer than their dislike for a transgressor who hurt them a little, but precisely the opposite was the case. In Study 3, participants predicted that their dislike for a transgressor who hurt them a lot would last longer than their dislike for a transgressor who hurt someone else a lot, but precisely the opposite was the case. These errors of prediction are discussed as instances of a more general phenomenon known as the region-β paradox.